2008
DOI: 10.1161/circulationaha.107.729889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Italian Smoking Ban on Population Rates of Acute Coronary Events

Abstract: Background-Several countries in the world have not yet prohibited smoking in public places. Few studies have been conducted on the effects of smoking bans on cardiac health. We evaluated changes in the frequency of acute coronary events in Rome, Italy, after the introduction of legislation that banned smoking in all indoor public places in January 2005. Methods and Results-We analyzed acute coronary events (out-of-hospital deaths and hospital admissions) between 2000 and 2005 in city residents 35 to 84 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
184
4
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(211 citation statements)
references
References 17 publications
16
184
4
7
Order By: Relevance
“…The fact that the studies from Italy (Barone-Adesi et al, 2006;Cesaroni et al, 2008) and Ireland showed smaller drops in AMI admissions than in the American locations may reflect lower levels of compliance with the law than in the US. In Italy and Ireland, implementation of the law was associated with 64% (Valente et al, 2007) and 69% (Mulcahy et al, 2005) reductions, respectively, in levels of secondhand smoke exposure, compared to an 84% reduction in the US (Travers et al, 2004).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The fact that the studies from Italy (Barone-Adesi et al, 2006;Cesaroni et al, 2008) and Ireland showed smaller drops in AMI admissions than in the American locations may reflect lower levels of compliance with the law than in the US. In Italy and Ireland, implementation of the law was associated with 64% (Valente et al, 2007) and 69% (Mulcahy et al, 2005) reductions, respectively, in levels of secondhand smoke exposure, compared to an 84% reduction in the US (Travers et al, 2004).…”
mentioning
confidence: 86%
“…Summary of studies of the effects of smokefree laws on acute myocardial infarction in Helena, Montana (Sargent et al, 2004), Pueblo, Colorado (Bartecchi et al, 2006), Piedmont, Italy (Barone-Adesi et al, 2006), Bowling Green, Ohio (Khuder et al, 2007), New York State (Juster et al, 2007), Ireland (Cronin et al, 2007), Saskatoon, Canada (Lemstra, Neudorf and Opondo 2008), and Rome, Italy (Cesaroni et al, 2008).…”
mentioning
confidence: 99%
“…6 A growing number of studies has shown evidence of reductions ranging from 8% to 40% in admissions to hospital for acute myocardial infarction after introduction of smoke-free legislation. [7][8][9][10][11][12][13] Very few studies have examined the impact of anti-smoking legislation on other cardiovascular outcomes or on respiratory outcomes.…”
mentioning
confidence: 99%
“…The introduction of legislation that prohibits smoking in indoor public spaces leads to an immediate reduction in inhalation of second-hand smoke by non-smokers, encourages smokers to attempt to quit smoking 1 , and reduces the prevalence of smoking 2,3 . Smoking ban legislation has been shown to lead to an immediate and significant reduction in acute myocardial infarction (AMI) risk in a number of studies [2][3][4][5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%